TRACING THE “CULTURAL CHANGES” IN SUNDANESE LOCAL INCANTATIONS - Musadad, Asep Nahrul (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
One of the key terms employed in exploring the story of Islamization in the archipelago is the acculturation between Islamic spectrum and local genius, through which the fie grain of Islamization flws. This paper aims to discuss this acculturation with special reference to the “cultural change” mechanism that reflcted in Sundanese local incantations. To some extents, it has reflcted the indigenous articulation of Islamic spectrum. In the tradition of Sundanese oralliterature, particularly those are widely used by “pananyaan” (local shaman), there are several magical spells that creatively assimilate with the Islamic symbols. Using the ethnographic method and Haviland’s notion of the stages of “cultural change”, it provides a preliminary exploration on how they adopted as supplement or even transformed into local incantations and how the cultural change, in turn, synthetically happens. The research shows the various form of incantations; from hybrid incantations to pure Arabic “amalan”. They reflcted the presence of three kinds of mechanism as follows: (1) “the innovation” that reflcted in several mixture incantations, (2) “the diffsion” as represented by several incantations which indicated to have their origin from outside region, and (3) “the cultural loss” which represented by incantations in the Arabic formulas. This kind of assimilation has shown the reception of Sundanese people which also established by local determinations. In one sense, it also reflcted – in Ricklefs term – the “mystic synthesis” which regarded as the one of the “major gate” for Islamization of the archipelago.